Adaptation of The Brand Pride Scale into Turkish: Validity and Reliability Study (Third Sector Social Economic Review, 2025)
This study aims to adapt the Brand Pride Scale into Turkish and to test its validity and reliability. Brand pride is an important construct that influences various consumer behaviors as a result of the emotional and psychological bond consumers develop with a brand. Consumers who feel proud of a brand tend to exhibit a stronger sense of belonging, which is reflected in behaviors such as brand loyalty, repurchase intention, positive word-of-mouth communication, and brand advocacy. In this regard, developing the Turkish version of the scale, examining the psychometric robustness of the measurement instrument, and contributing to the Turkish literature constitute the main purpose of the study. The Brand Pride Scale adopted in this research focuses on measuring the degree of pride consumers feel toward a brand. During the adaptation process, the scale was translated to preserve semantic integrity while maintaining consistency with its original structure in the Turkish language context. The study sample consisted of 484 participants from different age groups and socio-economic levels. The data obtained were analyzed using confirmatory factor analysis. The results revealed that the two-dimensional structure of the scale (individual brand pride and collectivist brand pride) retained its validity in the Turkish sample. Furthermore, Cronbach’s alpha coefficients and composite reliability values indicated that the scale demonstrates a high level of reliability. Overall, the findings suggest that the Brand Pride Scale is a valid and reliable measurement instrument for Turkish consumers.
Keywords: brand; brand pride; Scale Adaptation; Validity and Reliability; Consumer Behavior